Fly-ash derived Na-P1, natural zeolite tuffs and diatomite in motor oil retention - Maria Roulia; Konstantina Koukouza; Michael Stamatakis; Charalampos Vasilatos (Cleaner Materials, 2022)
Aluminosilicate materials of various grain sizes, i.e., Kimolos, Samos and Sorano zeolite tuffs, Samos diatomite and synthetic zeolite prepared from Meliti fly ash via alkaline hydrothermal treatment, were tested as new sorbents for oil leakage remediation. Two lubricant oils of different viscosity, i.e., SHELL HELIX HX5 20 W-50 and ULVAC SMR-100 were selected as potential adsorbates. All sorbents employed demonstrated exceptional oil retention capacity values exceeding 100% (w/w); specifically, Kimolos and Sorano zeolites as well as thermally treated Samos diatomite proved best reaching 160% (w/w) oil sorption. Mordenite and phillipsite were mostly detected in Kimolos and Italian zeolite tuffs, respectively. Na-P1 zeolite, produced for the first time from Meliti fly ash without pretreatment via a low-temperature hydrothermal procedure, was characterized by XRD and SEM. The zeolitization process, leading to Na-P1 as the sole synthesis product, was carried out without the use of additives. The synthetic Na-P1 zeolite displayed significant sorption capacity, retaining 125 and 105% (w/w) of the viscous and less viscous oils tested, respectively. Thus, valorization of all aluminosilicate materials employed was achieved. Both porosity measurements and SEM micrographs demonstrated that the highest lubricant oil retention values were reached by macroporous adsorbents having open structure and large surface area, suitable for overcoming the fluid’s resistance to flow and avoiding pore-blocking effects.